Transformasi Digital Pelayanan Publik Berbasis E-Government: Analisis Efisiensi, Transparansi, dan Aksesibilitas di Disdukcapil Provinsi Maluku - Dominggas Saliama; Hengky Virgo Richardo Pattimukay (MAN 4 Kota Pekanbaru, 2026)
Digital transformation in the government sector has become one of the primary strategies for improving the quality of public services. The implementation of e-government enables the government to deliver services that are more effective, transparent, and responsive to the needs of the community. This study aims to analyze how digital transformation through the implementation of e-government can enhance the quality of public services at the Department of Population and Civil Registration of Maluku Province. This research employs a descriptive qualitative approach, with data collection techniques including observation, interviews, and documentation studies. The findings indicate that the implementation of digital-based services has improved service efficiency, accelerated service processing time, and enhanced bureaucratic transparency and accountability. However, the implementation of e-government still faces several challenges, including limited technological infrastructure, low levels of digital literacy among the public, and the capacity of human resources within the bureaucracy. Therefore, it is necessary to strengthen the capacity of public officials, enhance digital infrastructure, and integrate electronic-based service systems to ensure that digital transformation can be implemented optimally.